Implementasi Failover Router MikroTik Untuk Meningkatkan Ketersediaan Jaringan Pada Fakultas Teknik Universitas Pancasila - Husein Zidan; Zahra Jane Arnecia; Leni Oktaviani; Gina Anisa; Bambang Riono Arsad (Journal of Informatics and Advanced Computing (JIAC), 2024)
Technology can help manage connectivity that can support data exchange in the network. Using a well-designed topology can improve network performance optimally. The use of computer networks in agencies can enable data exchange via hardware and software that are connected to each other in a network. Topology implementation can be adjusted to user needs. In this research, the author used the Informatics Engineering Study Program building at Pancasila University as an object. Please be aware that the network can experience problems, such as stopping system performance which can hinder the data exchange process that is taking place. The solution provided can be in the form of implementing failover using a MikroTik router. MikroTik routers can be used as backup routers in server infrastructure and failover is an automatic or manual process for switching from a system or component that is failing to a backup system or component that is functioning properly. This can be a strategy and factor in increasing network availability in the Pancasila University engineering faculty building. The final result of the analysis carried out is a MikroTik failover design that will be used in the Pancasila University Faculty of Engineering building.